The Influence of Motivation, Interest, Learning Readiness, and Study Facilities on Vocational Student Achievement - Desmiarni Desmiarni; Waskito Waskito; Nizwardi Jalinus; Fadhilah Fadhilah; Lasyatta Syaifullah (Postgraduate, University of Mataram, 2025)
Vocational education success depends heavily on multiple interconnected factors that influence student academic performance. This study examines the influence of motivation, interest, learning readiness, and study facilities on student learning outcomes in Computer and Basic Networking courses at SMK Negeri 2 Sungai Penuh. Research employed a quantitative approach with a causal correlational design, involving 71 students selected through proportional stratified random sampling. Data was collected using structured questionnaires and analyzed through path analysis. Results revealed that all independent variables significantly influence learning outcomes, with interest having the strongest impact (standardized coefficient=0.392, p<0.001), followed by learning readiness (0.366, p<0.001), motivation (0.212, p<0.001), and study facilities (0.056, p<0.05). Collectively, these variables explain 99.4% of the variance in learning outcomes (R²=0.994). The findings highlight the critical role of student interest in technical subjects and emphasize the importance of a holistic approach that addresses both internal factors (motivation, interest, readiness) and external conditions (facilities). These results suggest that vocational schools should prioritize strategies to enhance student interest through interactive learning methods, ensure adequate learning facilities, and develop comprehensive student readiness programs to optimize educational outcomes.